2019
DOI: 10.1128/aem.00465-19
|View full text |Cite
|
Sign up to set email alerts
|

Infection Rates and Alkaloid Patterns of Different Grass Species with Systemic Epichloë Endophytes

Abstract: Symbiotic Epichloë species are fungal endophytes of cool-season grasses that can produce alkaloids with toxicity to vertebrates and/or invertebrates. Monitoring infections and presence of alkaloids in grasses infected with Epichloë species can provide an estimate of possible intoxication risks for livestock. We sampled 3,046 individuals of 13 different grass species in three regions on 150 study sites in Germany. We determined infection rates and used PCR to identify Epichloë species diversity based on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 80 publications
(135 reference statements)
0
25
1
Order By: Relevance
“…Climate change could result in environmental conditions that are more conducive to survival of infected grasses, which may increase their distribution to a level that endophyte-infected plants could dominate grasslands. Previous studies on grasslands in Germany and Spain showed that single individuals of cool season grass species infected with Epichloë can contain alkaloid concentrations above the toxicity thresholds for livestock [35,46,55], which for ergovaline are 300-500 ppb for cattle and horses, and 500-800 ppb for sheep, with lolitrem B concentrations toxic at 1800-2000 ppb [48]. In typical meadows, the infected toxic grasses are diluted by a high diversity of other species and low infection frequencies, so have been of little concern for causing toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Climate change could result in environmental conditions that are more conducive to survival of infected grasses, which may increase their distribution to a level that endophyte-infected plants could dominate grasslands. Previous studies on grasslands in Germany and Spain showed that single individuals of cool season grass species infected with Epichloë can contain alkaloid concentrations above the toxicity thresholds for livestock [35,46,55], which for ergovaline are 300-500 ppb for cattle and horses, and 500-800 ppb for sheep, with lolitrem B concentrations toxic at 1800-2000 ppb [48]. In typical meadows, the infected toxic grasses are diluted by a high diversity of other species and low infection frequencies, so have been of little concern for causing toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Endophyte infection was performed at the Noble Research Institute, LLC, Ardmore, Oklahoma, USA, using a multiplex PCR with endophyte specific primers on DNA extracted from individual seeds randomly selected from each of the seed mixtures, as described previously [35]. Each seed lot was tested twice.…”
Section: Endophyte Detection By Multiplex Pcrmentioning
confidence: 99%
See 3 more Smart Citations